Efektivitas Bahasa Isyarat dalam Pembelajaran Mengaji bagi Santri Tunarungu: Studi Kasus di Masjid Raya Al-Adzhom - Al Fahmi, Faiz Fikri; Zakiah, Risalatu; Wiyanto, Hari; Mukaromah, Lailatul; Jaya, Rizki Rahmat; Alifah, Rafa; Giffari, Ahmad (Malewa: Journal of Multidisciplinary Educational Research, 2025)
This study aims to examine the effectiveness of using sign language in the learning process of reciting the Quran for deaf students, by taking a case study at the Al-Adzom Grand Mosque. Deaf students, as children with special needs, face limitations in hearing, but still show high enthusiasm and motivation in studying the Quran. In this context, sign language becomes an alternative communication medium that allows them to understand the learning material more optimally. This study uses a qualitative approach with data collection methods in the form of in-depth interviews with Quran teachers and student caregivers, as well as literature studies that support theoretical understanding. The data were analyzed descriptively to describe how the application of sign language affects the ability of deaf students to read and understand the verses of the Quran. The results of the study showed that the use of sign language was proven to be effective and had a positive impact on the development of the students' Quran reading skills. This finding confirms that physical limitations are not the main barrier in the process of religious education, as long as the methods applied are able to accommodate the special needs of students. Therefore, it is important for Islamic educational institutions to develop an inclusive and adaptive approach for students with disabilities.